SPME-GC-MS & metal oxide E-Nose 18 sensors to validate the possible interactions between bio-active terpenes and egg yolk volatiles. (November 2019) - Gouda, Mostafa; Ma, Meihu; Sheng, Long; Xiang, Xiaole
Abstract: This study was focused on the differences between three concentrations of four safe bio-active volatile terpenes and natural compounds (trans-cinnamaldehyde, thymol, menthol, and vanillin) on the egg yolk volatile components. In which, Headspace Solid phase Micro Extraction (HS-SPME) followed by GC/MS were used for volatiles analysis, and electronic nose (E-Nose) with 18 sensors was used for the aroma pattern. In the results, a total of 111 different volatile compounds were identified by using GC/MS. Some ketones, amines, nitro and organic acid compounds such as hexanone were significantly reduced after using these compounds. On the other hand, first principal components (PC1) of trans-cinnamaldehyde (0.1%) was decreased significantly ( p < .05) to −4.8 ± 0.8, compared to the control with 4.3 ± 2.1. And, it increased benzaldehyde and nonanal peaks area significantly to 46.56 ± 14.46 and 9.22 ± 4.81 MPA. In menthol (0.1%), the content of d-limonene was decreased to 4.65 ± 0.49 MPA, compared to the control with 14.16 ± 4.95 MPA. On the other hand, by E-Nose, vanillin (0.1%) PC1 was decreased significantly to −4.48 ± 0.43. Moreover, thymol (0.1%) decreased hydrocarbon sensation to 0.448 ± 0.005. And, vanillin (0.1%) decreased hydrogen sulfide and ketones sensation to 0.169 ± 0.01 and 0.344 ± 0.01, respectively. In conclusion, this study is providing novel information to understand the effects of bio-active molecules on the biological fatty media volatility. Also, it explains how terpenes can protect egg yolk media from the unacceptable odor formation which results from the degradation of its lipids and proteins. Graphical abstract: Unlabelled Image Highlights: One hundred eleven different volatile compounds were found by HS-SPME-GC/MS. Hexanal, nonanal, and benzaldehyde showed positive volatiles PC1 and negative PC2. Trans-cinnamaldehyde and thymol significantly decreased yolk ketones. Azulene was formed in trans-cinnamaldehyde and thymol (0.1%). A significant negative correlation was found between PC1 of volatiles and E-nose.